Assessment of Knowledge Level and Awareness About Human Papillomavirus Among Dental Students - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA; YILMAZ, GÖZDE (SPRINGER, 2021)
Epidemiological studies have shown that the worldwide trend of human papillomavirus (HPV)-induced oral cancer has increased. Dentistry students need comprehensive information about HPV to provide accurate advice to their patients. The aim of this study is to evaluate 3rd, 4th, and 5th grade students' knowledge and awareness about HPV. A questionnaire consisting of 16 questions was applied to 318 students (100 3rd grade, 119 4th grade, and 99 5th grades), who were studying at XXX. In this survey, students' knowledge level and awareness were examined. In our study, 99 (31.0%) of the participants were male and 219 (68.9%) were female. There was a statistically significant difference between the classes in terms of participation rates in the statement Some types of HPV cause oral cancer (p, 0.000; p < 0.05). The rate of participation of third grade (72%) students in this proposition was significantly lower than 4th grade (89.9%) and 5th grade (84.8%) students (p1, 0.000; p2, 0.000; p < 0.05). There was no statistically significant difference between 4th and 5th grade students (p > 0.05). Overall, advanced students showed better knowledge, attitudes, and perceptions regarding human papillomavirus-related oral cancer. Comprehensive training and motivation for improving dentistry students' awareness against HPV-induced oral cancer will also improve knowledge and attitudes of the dental students.
Keywords: HPV; Oral cancer; Dental students; Awareness; SQUAMOUS-CELL CARCINOMAS; OROPHARYNGEAL CANCER; HEAD; EPIDEMIOLOGY; INFECTION; RISK